Meningkatkan Produktivitas Mesin Pengupas Kulit Nanas dengan Sistem Pneumatik Ganda - Arfandy, Arfandy; Mihdar, Uswatul Hasanah; A. Ariputra; Halim, Abdul; Muttaqin, Ahmad Nurul (Jurnal Teknik Mesin Indonesia, 2024)
This research explores the evolution of technology in pineapple peeling, from the use of manual knives to sophisticated pneumatic technology. The main focus is on pineapple peeling machine design, working principles, and calculating time efficiency between machine and manual peeling. The aim is to broaden students' understanding of designing machines and provide guidance for students in applying pneumatic technology. The study began with literature observations and field studies to collect price and specification data as well as information components about pineapple. Next, planning, manufacturing, and testing of the machine are carried out. Data was collected from both stripping processes for further analysis. The research results include machine designs with main components such as actuators, knife blades, knife fasteners, and machine frames, as well as pneumatic component specifications, which are explained in detail. A comparison of stripping times shows a significant increase in efficiency with the machine, with the fastest time of 9.09 seconds and the longest time of 447 seconds for manual stripping. This research contributes to the development of pineapple processing technology and increases efficiency in the fruit processing industry as a whole.